DYNAMIC CHANGES OF CYTOKINE LEVELS IN THE BLOOD SERUM OF PATIENTS WITH MODERATE ACUTE CHOLECYSTITIS AND HIGH OPERATIONAL AND ANESTHETIC RISK DEPENDING ON THE SURGICAL TREATMENT - V.V. Moroz; Yu.M. Zakharash; N.G. Bychkova (Bogomolets National Medical University, 2016)
Summary. TG 13: Updated Tokyo Guidelines for the management of acute cholangitis and cholecystitis do not provide complete answers, how to determine the volume of the surgical intervention while treating patients with moderate acute cholecystitis and high operational and anesthetic risk (Grade II). In order to solve this problem it is necessary to determine timing and volume of surgical interventions, to establish additional criteria for the selection and conformation of the effectiveness of the selected tactics, to have a possibility to predict outcomes. Aim. To improve treatment results and determine the efficiency of different types of surgical interventions in patients with moderate acute cholecystitis (Grade II) considering the dynamic changes of the cytokine profile in blood serum of patients. Materials and methods. The study included 76 patients with moderate acute cholecystitis (Grade II). The severity of the general physical condition was determined by the ASA scale. Patients were divided into 2 groups: Group 1 (39 patients) and Group 2 (37 patients). Patients from the Group 1 passed conservative therapy, which with no effect after 24 hours was supplemented with emergency laparoscopic cholecystectomy. In the Group 2 in the first stage of treatment along with conservative therapy, there were performed ultrasound guided puncture draining interventions for the acute cholecystitis and inflammatory complications treatment in the early hours of the patient hospitalization. In all patients in both groups, there were determined levels of cytokines in blood serum: TNF-a, IL-4, IL-6, IL-8, TGF-p. Results and discussion. The surgical tactics in the Group 1 led to an increase of acute cholecystitis clinical signs and in 8 (20.8 %) patients to the development of severe forms of acute cholecystitis and inflammatory complications; it led to the increase of all cytokines in blood serum and their delay at increased level after emergency laparoscopic cholecystectomy performance and the development of inflammatory complications in 12.8 % patients. Mortality in Group 1 was 5.1 %. Surgical tactics in the Group 2 reduced the number of emergency laparoscopic cholecystectomy performances and it decreased the incidence of postoperative complications up to 8.1 %. Delayed laparoscopic cholecystectomy was performed in 94.6% patients in the Group 2, and the conversion frequency was 5.4% (in the Group 1 it was 28.2%). Conclusions. The performance of ultrasound guided puncture-draining endo-biliary interventions in the case of acute cholecystitis and its complications leads to the decrease of cytokine levels and thus allows to perform radical surgery as the second stage of surgical treatment and to reduce the incidence of postoperative complications and minimize mortality.